Measurements of electroweak Wjj production and constraints on anomalous gauge couplings with the ATLAS detector - Onofre, A. (2017)
Measurements of the electroweak production of a W boson in association with two jets at high dijet invariant mass are performed using s√= 7 and 8 TeV proton–proton collision data produced by the Large Hadron Collider, corresponding respectively to 4.7 and 20.2 fb−1 of integrated luminosity collected by the ATLAS detector. The measurements are sensitive to the production of a W boson via a triple-gauge-boson vertex and include both the fiducial and differential cross sections of the electroweak process.